1990
DOI: 10.1080/14640749008401236
|View full text |Cite
|
Sign up to set email alerts
|

On the Representation and Processing of Compound Words: Automatic Access to Constituent Morphemes Does Not Occur

Abstract: Three lexical decision experiments using a variant of the semantic priming technique tested the hypothesis that compound words are morphologically decomposed during recognition. If a compound constituent is accessed during processing, an associative prime will facilitate that access and hence recognition of the whole word. Contrary to the predictions derived from the automatic decomposition hypothesis, Experiment 1 revealed no priming effects for semantically opaque compounds (buttercup) and pseudo-compounds (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
145
6
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(176 citation statements)
references
References 45 publications
14
145
6
6
Order By: Relevance
“…In the psycholinguistics literature, the various data obtained in visual word recognition using different experimental paradigms, such as cross-modal and unimodal priming, as well as in reading with different tasks (e.g., lexical decision, naming, eye movement monitoring, and progressive demasking) do not converge to an extent that they would allow a validation of one particular model (Andrews, 1986;Hyönä & Pollatsek, 1998;Inhoff, Radach, & Heller, 2000;Jarema, Busson, Nikolova, Tsapkini, & Libben, 1999;Kehayia et al, 1999;Libben, 1994;Monsell, 1985;Pollatsek, Hyönä, & Bertram, 2000;Sandra, 1990;Taft & Forster, 1976;Zwitserlood, 1994). Using visually presented nonwords, Taft and Forster (1976) showed that the response latencies in a lexical decision task were influenced by the lexical status as well as by the frequency of the left constituents.…”
Section: Previous Researchmentioning
confidence: 99%
“…In the psycholinguistics literature, the various data obtained in visual word recognition using different experimental paradigms, such as cross-modal and unimodal priming, as well as in reading with different tasks (e.g., lexical decision, naming, eye movement monitoring, and progressive demasking) do not converge to an extent that they would allow a validation of one particular model (Andrews, 1986;Hyönä & Pollatsek, 1998;Inhoff, Radach, & Heller, 2000;Jarema, Busson, Nikolova, Tsapkini, & Libben, 1999;Kehayia et al, 1999;Libben, 1994;Monsell, 1985;Pollatsek, Hyönä, & Bertram, 2000;Sandra, 1990;Taft & Forster, 1976;Zwitserlood, 1994). Using visually presented nonwords, Taft and Forster (1976) showed that the response latencies in a lexical decision task were influenced by the lexical status as well as by the frequency of the left constituents.…”
Section: Previous Researchmentioning
confidence: 99%
“…Semantically transparent compounds such as snowball fight are usually distinguished from semantically opaque compounds, which are not related to the meaning of their constituting morphemes (e.g. deadline keeping : Sandra 1990;Zwitserlood 1994). …”
Section: Accessing Morphologically Complex Formsmentioning
confidence: 99%
“…That is, the meaning of each constituent is accessed during understanding a compound, presumably in order to integrate all constituent meanings. Sandra (1990) reported facilitated word recognition in Dutch, i.e. shorter reaction times for written compounds that were preceded by associatively related, written mono-morphemic nouns compared to compounds preceded by unrelated nouns.…”
Section: Introductionmentioning
confidence: 99%